2023
DOI: 10.1080/13218719.2023.2192257
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mental illness in young people in custody over time: a comparison of three surveys in New South Wales

Abstract: Few studies have examined the prevalence of mental illness in young people over time within the same jurisdiction. In the current study, we compared data from three large surveys of youth in custody in New South Wales, conducted in 2003, 2009 and 2015. We examined rates of mental illness, self-harm and suicidal behaviours, substance use and childhood trauma and found little consistent change over time, though some fluctuations were observed regarding certain mental illnesses and substance use. We also descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 1 In New South Wales (NSW), 39%–63% of young people supervised in custody are diagnosed with at least one psychiatric disorder. 2 Previous research has demonstrated an increased risk of criminal justice involvement and recidivism among young people with psychiatric disorders. 3 The relationship between psychiatric morbidity and criminal justice involvement is particularly complex among adolescents, as they have high reoffending rates and sporadic incarceration episodes compared with adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 In New South Wales (NSW), 39%–63% of young people supervised in custody are diagnosed with at least one psychiatric disorder. 2 Previous research has demonstrated an increased risk of criminal justice involvement and recidivism among young people with psychiatric disorders. 3 The relationship between psychiatric morbidity and criminal justice involvement is particularly complex among adolescents, as they have high reoffending rates and sporadic incarceration episodes compared with adults.…”
Section: Introductionmentioning
confidence: 99%
“… 7 In NSW, the self-reported lifetime prevalence of psychiatric hospitalisations among young people in custody ranges between 13% and 17%. 2 Majority of studies that investigate mental health issues among justice-involved youth primarily focus on those in custody, often overlooking youth under community supervision. 8 These gaps in knowledge could potentially lead to interventions missing critical factors influenced by family and environmental contexts, resulting in suboptimal rehabilitation, worsening mental health conditions and increased recidivism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation